Hubungan Locus of Control Internal Dengan Kematangan Karir Siswa - Mulia Siregar (Mahesa Research Center, 2021)
This research aims to study and prove a correlation between internal locus of control and the career maturity to the students of SMKN (State Vocational School) 1 Percut Sei Tuan. The hypothesis in this research is there is a positive correlation between internal locus of control and the career maturity it means the higher of internal locus of control the higher of career maturity. The internal locus of control is measured using I-E scale that arranged by Rotter (1966) and adapted by researcher. The career maturity is measured by CMI that arranged by Crites and adapted into the culture of Indonesia by Taganing, et. al. (2006). This research involves 90 students in Grade XI and XII of SMKN 1 Percut Sei Tuan in Mapping survey and Construction of Concrete department. The sample is taken by total sampling method because the researcher take total population as sample of this research. Based on the results of research it concluded that there is a significant correlation between variable X – Y, with rxy = 0.674; p = 0.000 (p < 0.010) means the hypothesis is accepted. The effective contribution of internal locus of control to the career maturity is 45.5%.